Sistem Telemonitoring Kekeruhan dan pH Air Terhadap Pengurasan Serta Pemberian Kaporit Otomatis Dalam Kolam Renang Berbasis - Kalam Achmad Nabila; Aisah Aisah; Abdul Rasyid (Politeknik Negeri Malang, 2022)
Swimming is an activity that popular. However without realized, the water of swimming pools have a not good enough quality, so that it becomes a medium for the transmission of various diseases in water. Monitoring quality of swimming pool water is a sanitation effort, namely by providing liquid chlorine to reduce organic substances and as disinfection against microorganisms. With this problem, the authors conducted research on telemonitoring system of turbidity and ph of water for draining and providing automatic chlorine in smartphone-based swimming pools. The system applied to a miniature swimming pool consisting of four sensors, namely pH sensor, turbidity sensor, ultrasonic sensor, waterflow sensor, the four sensors will send data to ESP32 to be processed according to the system. After ESP32 has finished processing it is then sent to firebase and an application on a smartphone to make water monitoring and control easier. The test results can be concluded that system designed using ESP32 as a microcontroller will process data from the pH sensor, turbidity sensor, waterflow sensor and ultrasonic sensor. Then the results of pH data have highest pH value of 7.9 and lowest of 6.9. Furthermore, results of the turbidity sensor data have a value of 0 NTU with highest ADC of 3827. The drain is automatically divided into 2, namely monitoring and controlling. Furthermore, the quality of WiFi network tested using Wireshark when carrying out data transmission process in terms of delay has average value of 0.188389435, packet loss is 1.178 and throughput is 7428 Kb/s.